The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/jp407532j
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Carbon Nanotubes Using Mixed Surfactants: Experimental and Molecular Dynamics Simulation Studies

Abstract: The ability of cationic-rich and anionic-rich mixtures of CTAB (cetyltrimethylammonium bromide) and SDS (sodium dodecyl sulfate) for dispersing of carbon nanotubes (CNTs) in aqueous media has been studied through both the experimental and molecular dynamics simulation methods. Compared to the pure CTAB and SDS, these mixtures are more effective with the lower concentrations and more individual CNTs, reflecting a synergistic effect in these mixtures. The synergistic effects observed in mixed surfactant systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…The most stable dispersions were F.CNT-C110 and F.CNT-C100 which had an absorbance intensity close to 1, 1.05 and 1.25. As the absorbance value approached 1, it indicated that amount of dispersed CNT was increasing [5]. This UV-Vis spectrum corresponded to the dispersion test results in Fig.2.…”
Section: Uv-vis Spectra Of Cnt-ctabsupporting
confidence: 78%
“…The most stable dispersions were F.CNT-C110 and F.CNT-C100 which had an absorbance intensity close to 1, 1.05 and 1.25. As the absorbance value approached 1, it indicated that amount of dispersed CNT was increasing [5]. This UV-Vis spectrum corresponded to the dispersion test results in Fig.2.…”
Section: Uv-vis Spectra Of Cnt-ctabsupporting
confidence: 78%
“…The physical adsorption of surfactant on the nanotubes surface reduces the surface tension of CNTs, effectively preventing the formation of aggregates. Also, the presence of an aromatic group in the surfactant molecule allows for π-π stacking interactions with the graphitic sidewalls of the nanotubes, which results in their effective coating and dispersion [47,48] .…”
Section: Non-covalent Functionalizationmentioning
confidence: 99%
“…The ability of cationic-rich and anionic-rich mixtures of (cetyltrimethylammonium bromide) CTAB and SDS for dispersing of CNTs in aqueous media has been studied by Sohrabi et al [35] through the MD simulation method. They found that; compared to the pure CTAB and SDS, these mixtures are more effective with the lower concentrations and more individual CNTs, reflecting a synergistic effect in these mixtures.…”
Section: Dispersion Of Cnts By Surfactantmentioning
confidence: 99%